Incidences of the public agenda on citizens’ political attitudes through the theory of forgotten effects - Ortigosa Hernández, Mauricio (2021)
Fil: Ortigosa Hernández, Mauricio. Anáhuac University Mexico. School of Business and Economics; Mexico.